DAMPAK KUALITAS LAYANAN, HARGA DAN FASILITAS TERHADAP LOYALITAS PELANGGAN DI CAFE KATTAPA JEMBER - Putri, Angelita Leilia; Abdillah, Arya Abim; Permana, Bintang Rizky; Hidayat, Achmadani Nur; Qomariah, Nurul; Dhomas, Daâ€™i Dito (Fakultas Ekonomi dan Bisnis, 2025)
Micro, Small and Medium Enterprises or MSMEs are one of the important pillars of economic growth that have the potential to drive economic activity. Changes in people's lifestyles, which are increasingly changing by enjoying their free time in cafes, have caused the development of cafes to increase, marked by the number of new cafes with various services provided. Cafes currently face intense competition, and every company must maintain customer loyalty. This research aims to determine the influence of service quality, price and facility variables on customer loyalty at Cafe Kattapa in Jember. This research is quantitative research with a research population of Cafe Kattapa Jember customers. The sample used in this research was 100 people. The data collection method used in this research is by distributing questionnaires online. The data processing application used is IBM SPSS v.25. The results of this research state that service quality (X1), price (X2) and facilities (X3) have a positive and significant effect on customer loyalty (Y) at Cafe Kattapa Jember. The implication of this research is that customer loyalty can be built and increased by improving service quality, setting affordable prices and providing adequate facilities for businesses in the cafÃ© sector.